PUTUSAN PSBB PEMERINTAH INDONESIA DALAM MENANGGULANGI PANDEMIC COVID-19 TH. 2020 MELALUI PENDEKATAN HUMAN SECURITY DAN MAQOSHID - Ashadi, Willi (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2022)
he spread of the Covid-19 pandemic will occur in various countries in the world in 2020. This certainly makes the world’s goverments take steps to respond to the covid 19. Various ways have been taken to stop the spread of the pandemic, one of which is by implementing lock down policies in several countries such as Singapore, Russia, the People's Republic of China, South Korea and Indonesia. The lock down policy that was taken caused various problems in the social life of the community, especially in the economic field. Human security is a non-traditional security approach that is used to see the impact of a policy on people's lives in a country by considering aspects of health, economy, politics, environment, food, individuals and communities. Islam has a similar approach known as maqoshid syari'ah which includes points of religion, soul, mind, property and descent. With the magnitude of the impact caused by lockdowns in various countries of the world, the world government needs to pay attention to points of human security and maqoshid syari'ah to minimize the bad effects that occur. Keywords: Human Security, maqoshid syari'ah, covid-19, lockdown.